The Ettingshausen coefficient in quantum wells under influence of laser radiation in the case of electron-optical phonon interaction - Dao, Thu Hang; Dao, Thu Ha; Duong, Thi Thu Thanh; Nguyen, Quang Bau (Photonics Letters of Poland, 2016)
By using quantum kinetic equation for electrons interacting with optical phonon, the analytic expression for Ettingshausen coefficient (EC) in the quantum wells with parabolic potential (QWPP) under influence of laser radiation is obtained. The dependence of EC on the frequency, the amplitude of laser radiation, the quantum wells parameters and the temperature gradient are studied. The theoretical results are numerically calculated, plotted, and discussed for GaAs/GaAsAl quantum well. Especially, when we study the dependence of EC on temperature, we realize that the EC in QWPP is 102 times bigger than that in the bulk semiconductors. Full Text: PDF References A. Shik, Quantum wells (Physics and Electronics of two- dimensional systems) World Scientific (1999). Bau N. Q. and Hoi B. D., "INVESTIGATION OF THE HALL EFFECT IN RECTANGULAR QUANTUM WELLS WITH A PERPENDICULAR MAGNETIC FIELD IN THE PRESENCE OF A HIGH-FREQUENCY ELECTROMAGNETIC WAVE", Int. J. Mod. Phys. B 28 1450001 (2014). CrossRef Bau N. Q. and Hoi B. D., "Influence of a strong electromagnetic wave (laser radiation) on the hall effect in quantum wells with a parabolic potential", J. Korean Phys 60, 59 (2012). CrossRef Phong T. C. and Bau. N. Q., "Parametric Resonance of Acoustic and Optical Phonons in a Quantum Well", J. Korean Phys 42, 647 (2003). CrossRef Bau . N. Q, Hung L. T and Nam . N. D., "The Nonlinear Absorption Coefficient of a Strong Electromagnetic Wave by Confined Electrons in Quantum Wells Under the Influences of Confined Phonons", Journal of Electromagnetic Waves and Applications. 24, 1751, (2010). DirectLink Bau. N. Q and Trien. H. D, "The Nonlinear Absorption Coefficient of Strong Electromagnetic Waves Caused by Confined Electrons in Quantum Wires", J. Korean Phys.Soc. 56, 120 (2010). CrossRef Yu. S. G, K. W. Kim, M. A. Stroscio, G. J. Iafrate and A. Ballato, "Electron interaction with confined acoustic phonons in cylindrical quantum wires via deformation potential", J. Korean Phys 80, 2815 (1996). CrossRef M. Meziani, J. Lusakowski, W. Knap, N. Dyakonova, F. Teppe, K.Romanjek, M. Ferrier, R. Clerc,G. Ghibaudo, F. Boeuf, and T. Skotnicki, "Magnetoresistance characterization of nanometer Si metal-oxide-semiconductor transistors", J.Appl. Phys. 96, 5761 (2004). CrossRef N. Nishiguchi, "Excitation spectrum of a type-II superconductor in a very high magnetic field with randomly pinned vortices", Phys. Rev 52, 527 (1995). CrossRef P. Zhao, "Phonon amplification by absorption of an intense laser field in a quantum well of polar material", Sov.Phys. 49, 13589 (1994). CrossRef V.V.Pavlovich and E.M.Epshtein,Sov. Phys. Semicond 11, 809 (1977). Pankratov A. A.and Epshtein E. M., "Kinetic theory of longitudinal Hall effect in high frequency electric field", Sov. Phys. Semicond. [Fiz. Tekh. Poluprovodn.] 16 1689 (1982). Shmit.R., Semiconductors, Moskva, (Mir 1982). B.V.Paranjape and J.S.Levinger, "Theory of the Ettingshausen Effect in Semiconductors", Phys.Rev 120, 437 (1960). CrossRef V.L.Malevich and E.M.Epshtein, "Photostimulated odd magnetoresistance in semiconductors", Sov. Phys. Solid State [Fiz. Tverd. Tela ] 18 1286 (1976). V.L.Malevich and E.M.Epshtein, "Photostimulated kinetic effects in semiconductors", Sov. Phys, 18 (1976) 230. CrossRef E.M.Epshtein, "Theory of magnetoresistive and thermomagnetic effects with electron scattering by optical phonons in semiconductors", Sov. Phys 120, 226 (1976). CrossRef